2017
DOI: 10.1038/s41598-017-02082-8
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Inspired nacre-like nanolignocellulose-poly (vinyl alcohol)-TiO2 composite with superior mechanical and photocatalytic properties

Abstract: Nacre, the gold standard for biomimicry, provides an excellent example and guideline for assembling high-performance composites. Inspired by the layered structure and extraordinary strength and toughness of natural nacre, nacre-like nanolignocellulose/poly (vinyl alcohol)/TiO2 composites possessed the similar layered structure of natural nacre were constructed through hot-pressing process. Poly (vinyl alcohol) and TiO2 nanoparticles have been used as nanofillers to improve the mechanical performance and synchr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…More attention has been paid to the research of lignocellulose-based composites such as the lignocellulose-plastic composites 610 , lignocellulose/inorganic nanoparticles composites 1113 , fiber/organic phase composites 1418 . However, there have been only few literature reporting on the synthesis of high mechanical properties slab-like nanolignocellulose/inorganic composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More attention has been paid to the research of lignocellulose-based composites such as the lignocellulose-plastic composites 610 , lignocellulose/inorganic nanoparticles composites 1113 , fiber/organic phase composites 1418 . However, there have been only few literature reporting on the synthesis of high mechanical properties slab-like nanolignocellulose/inorganic composites.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been only few literature reporting on the synthesis of high mechanical properties slab-like nanolignocellulose/inorganic composites. It is thought that nanoparticles could dramatically induce an improvement in mechanical and electrical properties, heat resistance, radiation resistance 19 , and other properties as a result of the nanometric scale dispersion of the filler in the lignocellulose matrix 11 . These composites generally exhibit superior stiffness, strength, and heat distortion temperatures with respect to unreinforced polymers 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 b shows the XRD patterns of cellulose, nano-Fe 3 O 4 and NFF composites. The two diffraction peaks at 2 θ = 22.8° and 16.2°, standing for (002) plane and (101) plane, respectively, which were the characteristic peaks of cellulose [ 27 ]. It can be observed that the peaks appeared at 2 θ = 18.2°, 30.6°, 35.7°, 43.4°, 57.4°, and 62.9°, which stand for the (111), (220), (311), (400), (511) and (440) planes of the Fe 3 O 4 (PDF No.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, as the content of nano-Fe 3 O 4 increased, the relative intensities of diffraction peaks significantly increased. The average crystalline size of nano-Fe 3 O 4 particles on the fiber can be obtained by the Debye-Scherer equation [ 27 ]: where λ was the wavelength of the radiation, K was 0.89, 2 θ was the Bragg’s angle, and β was the full width at half maximum of (311) plane. The average crystalline size of the nano-Fe 3 O 4 particles was approximately 18.2 nm.…”
Section: Resultsmentioning
confidence: 99%
“…33 Likewise, the nacre-like nanolignocellulosepoly(vinyl alcohol)-TiO 2 composite microstructures have been used for photodegradation of methyl orange. 34 Whereas, the hierarchical ower-like Co 3Àx Fe x O 4 hollow microspheres and the hierarchically porous Fe 3 O 4 @SiO 2 @TiO 2 @Pt core-shell microspheres presented improved photocatalytic degradation of methylene blue and rhodamine B together with their rapid magnet-assisted separation. 35,36 Moreover, a polymer-templatedirected TiO 2 and the mixed TiO 2 /metal oxide (Al, Ga and In) microspheres have been developed for the efficient photocatalytic decomposition of 2-chlorophenol.…”
mentioning
confidence: 99%